The antibacterial effect of human adipose-derived stem cells on LL-37-resistant bacteria - Parisa Afzal Haghjoo; Ali Mojtahedi; Malek Moien Ansar; Malek Masoud Ansar; Safieh Danesh Mobarhan (PLoS ONE, 2025)
Human adipose-derived stem cells (hADSCs) exhibit antibacterial properties, but their effectiveness against bacteria resistant to LL-37- a natural human antimicrobial peptide important in the immune defense- is not fully understood. Some bacteria have evolved mechanisms to evade the antimicrobial effects of LL-37. We aimed to investigate the antibacterial efficacy of hADSCs against Pseudomonas aeruginosa, Proteus mirabilis, and methicillin-resistant Staphylococcus aureus (MRSA), focusing on the antimicrobial peptide LL-37. hADSCs were isolated from human adipose tissue, identified by flow cytometry and differentiation assays, and divided into three groups: unstimulated, stimulated with interferon-gamma (IFN-γ; 100 ng/mL) or Escherichia coli (300 CFU). LL-37 gene expression was measured by qPCR after 6 hours in the E. coli stimulated group. LL-37 peptide levels were quantified by ELISA in conditioned media from unstimulated, IFN-γ stimulated cells, both before and after incubation with pathogens (300 CFU). Antibacterial activity was assessed by colony counting incubation following incubation of conditioned media with bacteria. Conditioned media from both unstimulated and stimulated hADSCs significantly inhibited growth of all three pathogens ( P < 0.05), with highest efficacy against P. aeruginosa (86.4% inhibition), followed by MRSA (74%) and P. mirabilis (63%). LL-37 gene expression increased after bacterial stimulation, and also LL-37 concentrations increased in conditioned media but significantly decreased after bacterial exposure ( P < 0.05). Despite this reduction, antibacterial activity persisted. hADSC-conditioned media exert potent antibacterial effects against LL-37-resistant pathogens, even when LL-37 levels are reduced after bacterial exposure. These findings support the therapeutic potential of hADSC secretomes, particularly for infections caused by bacteria capable of reducing LL-37 levels.